Observations on the Endemic Pygmy Three-Toed Sloth, Bradypus pygmaeus of Isla Escudo de Veraguas, Panamá - Kaviar, Sam; Shockey, Jakob; Sundberg, Peter (PLOS ONE, 2012)
Our objective was to ascertain the population status of the Pygmy Three-toed Sloth, Bradypus pygmaeus, an IUCN Critically Endangered species, on Isla Escudo de Veraguas, Panama. Bradypus pygmaeus are thought to be folivorous mangrove specialists; therefore we conducted a visual systematic survey of all 10 mangrove thickets on the island. The total mangrove habitat area was measured to be 1.67 ha, comprising 0.024% of the total island area. The population survey found low numbers of B. pygmaeus in the mangrove thickets and far lower numbers outside of them. The connectivity of subpopulations between these thickets on the island is not established, as B. pygmaeus movement data is still lacking. We found 79 individuals of B. pygmaeus; 70 were found in mangroves and 9 were observed just beyond the periphery of the mangroves in non-mangrove tree species. Low population number, habitat fragmentation and habitat loss could lead to inbreeding, a loss of genetic diversity, and extinction of B. pygmaeus.